Platinum Group Elements in Howardites and Polymict Eucrites: Implications for Impactors on the HED Parent Body - Wee, Boon Siong; Yamaguchi, Yuji; Ebihara, Mitsuru (2010)
Most of the HED meteorites are breccias. These HED breccias consist of different proportions of eucrites, diogenites, and other minor components. Crystalline eucrites and diogenites generally have very low PGE (platinum group element) abundances due to metal-silicate fractionation. PGEs are strongly partitioned into FeNi metals (core). However, many HED breccias have relatively high abundances of PGEs. The presence of chondritic materials was inferred from siderophile elemental data [1] and carbonaceous chondrite clasts were found in howardites and polymict eucrites [2, 3]. Because of the low PGE abundances in crystalline rocks, PGEs can be used as signature elements to identify impactors [1,4]. By using PGE data of these polymict breccias, we aim to discuss the origin of impactor materials that caused wide spread brecciation on the parent body in the early solar system.